Mensch und Computer 2015 - Tagungsband Humans and Computers 2015 - Proceedings - Pielot, Martin (Mensch & Computer - Tagungsbände / Proceedings, 2015)
These conference proceedings include the specialized academic lecture and brief contributions presented at the Humans and Computers 2015 conference in Stuttgart. It provides multiple perspectives from research that collectively provide a kaleidoscope of ideas, theories, and methodologies. The conference bridges the gap between theory and practical implementation with numerous application-oriented essays.